Biological activity and chemical characterization of Pouteria lucuma seeds: A possible use of an agricultural waste - Guerrero-Castillo P. (2019)
The authors thank CONCYTEC (Convention 231-2015 FONDECYT) and FONDECYT REGULAR (Grant 1170871 and 1150745) for financial support.